Comparison of Secondary Crushing Operations Through Cone and Horizontal Shaft Impact Crushers - Köken, E.; Qu, Jili (International Multidisciplinary Scientific Geoconference, 2020)
Industrial size reduction processes such as crushing and grinding play vital roles in rock quarrying. The present study states real field data concerning secondary crushing operations through the cone and horizontal shaft impact (HSI) crushers. In this regard, a total of 44 case studies were collected from several rock quarries located in various parts of the world. Based on the field data, crushing performances of the cone and HSI crushers were compared by statistical analyses. The statistical analyses demonstrated that the specific energy consumption of HSI type crushers is relatively higher than those of cone crushers when comparing their production capacities. However, the difference in the specific energy consumption decreases with increasing the Los Angeles abrasion loss (LAA) of rocks. Specifically, the difference closes remarkably up when the LAA approaches 40%. It was also achieved that there is no remarkable superiority over the crushers with a specific energy consumption lower than 0.75 kWh/ton. Furthermore, the maximum feed size for cone and HSI crushers could be estimated at 12% of the mainframe opening and 39% of the rotor diameter, respectively. The ratios statistically found could be declared a start-up. These ratios are, therefore, beneficial for initial sizing related to secondary crushing operations. It was also claimed that for higher achievements in the production capacity (e.g.,> 8000 ton/day), cone crushers could be more feasible for handling rocks whose LAA is lower than 30%. Otherwise, the selection of secondary crushing equipment is associated with rock lithology, its reserve, economic constraints, targets, and marketplaces of rock aggregate manufacturers. © 2021 Elsevier B.V., All rights reserved.
Keywords: Comminution; Cone Crusher; Horizontal Shaft Impact Crusher; Rock Quarrying; Crushing; Energy Utilization; Lithology; Maps; Mine Shafts; Remote Sensing; Rocks; Size Determination; Statistical Methods; Surveying; Crushing Equipments; Crushing Performance; Economic Constraints; Horizontal Shafts; Industrial Size; Los Angeles Abrasion; Production Capacity; Specific Energy Consumption; Crushers